1995
DOI: 10.1046/j.1471-4159.1995.65031399.x
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Heme Oxygenase‐1 mRNA and Protein in Neocortex and Cerebral Vessels in Alzheimer's Disease

Abstract: Previous studies demonstrated the specific association of heme oxygenase (HO)‐1 protein to the neurofibrillary pathology of Alzheimer's disease (AD). In this study, we used reverse transcription‐polymerase chain reaction methods to show the increased expression of HO‐1 but not HO‐2 mRNA transcripts in cerebral cortex and cerebral vessels from subjects with AD compared with age‐matched non‐AD controls. Neither the HO‐1 nor the HO‐2 mRNA level was altered in the cerebellum, a brain region usually spared from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
88
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 201 publications
(95 citation statements)
references
References 17 publications
7
88
0
Order By: Relevance
“…Interestingly, the in vitro toxicity of amyloid-β is also abolished by pretreatment with metal chelators [53]. Data from our laboratory and others also indicate that heme oxygenase-1 (HO-1) is induced in AD brains [54,55]. HO-1 catalyzes the conversion of heme to biliverdin and iron.…”
Section: Redox-active Metalsmentioning
confidence: 78%
“…Interestingly, the in vitro toxicity of amyloid-β is also abolished by pretreatment with metal chelators [53]. Data from our laboratory and others also indicate that heme oxygenase-1 (HO-1) is induced in AD brains [54,55]. HO-1 catalyzes the conversion of heme to biliverdin and iron.…”
Section: Redox-active Metalsmentioning
confidence: 78%
“…Studies in a transgenic mouse model of AD showed that the expression of CuZn superoxide dismutase and HO-1 is significantly higher when compared with control mice [54]. Using immunolabeling or PCR techniques, a robust overexpression of HO-1 proteins, or mRNA in brain samples of sporadic AD when compared with age-matched controls was observed [58,64,66,68].…”
Section: Discussionmentioning
confidence: 99%
“…Heme oxygenase-1 (HO-1) is an antioxidant enzyme that degrades heme into biliverdin, iron and carbon monoxide and is one of the most sensitive and selective indicators of the cellular oxidative stress response. It has been shown that brains of AD patients present an increase of both HO-1 mRNA and protein [58,65] which co-localizes and parallels the expression of the altered form of tau characteristic of AD [76,77].…”
Section: −•mentioning
confidence: 99%
“…For the determination of heme oxygenase 1 (HO-1) mRNA levels, a real-time PCR technique was used (for review, see Bustin, 2000). A 271-base pair fragment of the HO-1 cDNA was amplified by using the LightCycler System (Roche Molecular Biochemicals, Indianapolis, IN) with the primers of Premkumar et al (1995). Quantitation was achieved by monitoring the fluorescence of intercalated SYBR Green I at each cycle.…”
Section: Methodsmentioning
confidence: 99%